NEGOSIASI KESAKRALAN DALAM PRAKTIK KEAGAMAAN HINDU DI ERA DISRUPSI DIGITAL (SEBUAH KAJIAN BUDAYA) - I Gede Parwata; Ni Nyoman Perni; Ida Ayu Adi Armini (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
Digital transformation reshapes Hindu religious practices through social media mediation, affecting ritual representation, religious authority, and believers’ religious experience. This article examines the negotiation of sacredness in Hindu practices in the era of digital disruption through cultural studies and the mediatization of religion framework. Employing a qualitative interpretive–critical paradigm, the study draws on digital ethnography, in-depth interviews, and media content analysis. The findings indicate that sacredness does not erode linearly; rather, it is negotiated through offline–online hybrid practices, curated ritual representations, and the strategic adaptation of religious authorities in digital spaces. Social media functions as a dialogical yet contested arena of religious meaning-making, prompting the reconfiguration of symbolic legitimacy and the fragmentation of authority. Believers’ responses display a spectrum of adaptations shaped by generational factors, digital literacy, and normative orientations. Theoretically, the study affirms sacredness as a symbolic construction negotiated within power relations and media logics. Practically, it underscores the need to strengthen digital religious literacy and develop ethical guidelines for ritual representation to sustain sacred meanings in digital public spaces.